Effects of TV advertising on children and parental influence on children's TV viewing - Joseph, C.; Ahmad, M. I. (Academy of Marketing Science, 1997)
The objective of this study is to investigate the effects of children advertising on children and parental influences on the children’s attitude and understanding levels toward children advertisements on television. The respondents for this study were both parents and children. Among others, the study revealed the children’s inability to distinguish commercials from TV programmes and to differentiate fantasy from reality. These inabilities, however, differed with children’s age levels. Further, the results indicate that parents have an influence over the children’s understanding levels with respect to children advertisements in television.